Towards Understanding the Origin of Cosmic-Ray Positrons - Aguilar M (AMER PHYSICAL SOC, 2022)
Precision measurements of cosmic ray positrons are presented up to 1 TeV based on 1.9 million positrons collected by the Alpha Magnetic Spectrometer on the International Space Station. The positron flux exhibits complex energy dependence. Its distinctive properties are (a) a significant excess starting from 25.2 +/- 1.8 GeV compared to the lower-energy, power-law trend, (b) a sharp dropoff above 284(-64)(+91) GeV, (c) in the entire energy range the positron flux is well described by the sum of a term associated with the positrons produced in the collision of cosmic rays, which dominates at low energies, and a new source term of positrons, which dominates at high energies, and (d) a finite energy cutoff of the source term of E-s = 810(-180)(+310) GeV is established with a significance of more than 4 sigma. These experimental data on cosmic ray positrons show that, at high energies, they predominantly originate either from dark matter annihilation or from other astrophysical sources.